The Influence of Islamic Financial Literacy and Islamic Good Corporate Governance (IGCG) on Donor Trust in Zakat Management Institutions: The Mediating Role of Accountability and Transparency - rizki, Ismi; Hendayana, Yana (Manunggal Halim Jaya, 2026)
The misuse of funds by ACT in 2022 shook public trust in zakat management institutions, reinforcing the urgency of Islamic financial literacy, accountability, transparency, and Islamic governance. This study analyzes the influence of Islamic financial literacy and Islamic Good Corporate Governance (IGCG) on donor trust, with accountability and transparency as mediating variables. Data were collected through a survey of 243 premium donors of Dompet Dhuafa West Java and analyzed using path analysis and the Sobel test. The results show that both Islamic financial literacy and IGCG have a significant effect on donor trust, both directly and indirectly through accountability and transparency. Transparency was found to be the stronger mediator. Collectively, the four variables explain 72.2% of the variance in donor trust. This study highlights the importance of strengthening Islamic financial literacy and internalizing IGCG principles as a strategy to build public trust and optimize sustainable zakat collection.